If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + -2 = 49 Reorder the terms: -2 + -7x = 49 Solving -2 + -7x = 49 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -7x = 49 + 2 Combine like terms: -2 + 2 = 0 0 + -7x = 49 + 2 -7x = 49 + 2 Combine like terms: 49 + 2 = 51 -7x = 51 Divide each side by '-7'. x = -7.285714286 Simplifying x = -7.285714286
| y=3lnx/2lnx | | 5-8z=-11 | | 180-x=165-2(90-x) | | y=1-6x^2 | | 5x+12=-3x+36 | | 10-3x=2.5x | | 7a+6a-11+15-17+20-6a=-7 | | 1/7•7 | | 25x+7.5x^2=0 | | -16t^2+26t=5 | | 2.5x(10-3x)=0 | | h=-16t^2-44t+6 | | 5(12y-12)+37=60y-23 | | 2v+43=5(v+5) | | 5m-4+7-8m+4m=-3 | | 4x-2x=16/2 | | (x+4)(4-x)=0 | | -4(u-5)=-2u+6 | | (48-x^2)/(4x) | | H(-x)=x^4+3x^2+8 | | 3x+14=10x+14 | | y-11/2=5(x-11/2) | | -2v+44=-8(v-7) | | 20=70*NA+90*NB | | 7x+17=5x+17 | | 20=70xNA+90xNB | | 4(x+3)=8(8+5x-4) | | 5(x+5)=6+5x | | 20=70x+90b | | 4(x+3)=8(8+x-1) | | 36-4*3*2=0 | | 36-4*3*2=9 |